Overview of guidance for endoscopy during the coronavirus disease 2019 pandemic - Lui, Rashid N; Wong, Sunny H; Sánchez‐Luna, Sergio A; Pellino, Gianluca; Bollipo, Steven; Wong, Mei‐Yin; Chiu, Philip W Y; Sung, Joseph J Y (Journal of gastroenterology and hepatology, 2020)
From its beginning in December 2019, the coronavirus disease 2019 outbreak has spread globally from Wuhan and is now declared a pandemic by the World Health Organization. The sheer scale and severity of this pandemic is unprecedented in the modern era. Although primarily a respiratory tract infection transmitted by direct contact and droplets, during aerosol‐generating procedures, there is a possibility of airborne transmission. In addition, emerging evidence suggests possible fecal–oral spread of the virus. Clinical departments that perform endoscopy are faced with daunting challenges during this pandemic. To date, multiple position statements and guidelines have been issued by various professional organizations to recommend practices in endoscopic procedures. This article aims to summarize and discuss available evidence for these practices, to provide guidance for endoscopy to enhance patient safety, avoid nosocomial outbreaks, protect healthcare personnel, and ensure rational use of personal protective equipment. Responses adapted to national recommendations and local infection control guidelines and tailored to the availability of medical resources are imminently needed to fight the coronavirus disease 2019 pandemic.